FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN ROKOK YANG LISTING DI BURSA EFEK INDONESIA - Warnika Febri Astanty (JURNAL RISET AKUNTANSI JAMBI, 2023)
This study aims to determine the factors that affect the stock prices of cigarette companies listed on the Indonesia Stock Exchange during the Covid-19 pandemic. By using monthly data obtained from the datastream as well as using linear regression panel data. To test the relationship that occurs, two indicators of the company's financial performance are used which then become dependent variables, namely Dividend Per Yield and Price Earning Ratio and one independent variable, namely Stock Price. This research found that Dividend Per Share has a significant relationship with the Share Price of cigarette companies listed on the Indonesia Stock Exchange during 2021 while the Price Earning Ratio has no relationship at all.